Pemanfaatan Hasil Pangan Lokal dalam Upaya Pencegahan Stunting di Desa Bandar Baru, Kecamatan Sibolangit, Sumatera Utara - Yulmaniati Yulmaniati; Nabiilah Hurul Ainun; Muhamma Jailani (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The purpose of this service is to increase nutritional knowledge, improve milk processing skills for housewives, especially pregnant and lactating women, and young women. These objectives can be achieved through various corrective activities including: (1) General counseling and nutrition, (2) Counseling on the nutritional composition and benefits of corn, (3) Extension of various corn products, (4) Training on corn milk processing. The method used in this service is Participatory Action Research (PAR) for a month at the service partners of Bandar Baru Village. The results of this activity indicate that (1) there is an increase in public knowledge about food and nutrition as well as innovation in corn processing. (2) the community has the skills to convert corn products into milk. (3) Knowledge and skills that can be used as business pilots to meet the needs of people's lives, so that stunting can be minimized.